1998
DOI: 10.1038/sj.bjc.6690027
|View full text |Cite
|
Sign up to set email alerts
|

Absence of mutation of the p73 gene localized at chromosome 1p36.3 in hepatocellular carcinoma

Abstract: Summary Accumulating evidence has demonstrated that aberration of the p53 tumour-suppressor gene is one of the pivotal genetic events in hepatocellular carcinogenesis. Recent reports suggest that the product of hepatitis B virus (HBV) interacts with p53 and that the hepatitis C virus (HCV) core protein reduces p53 expression. A novel p73 gene, which is related to p53, has recently been identified and mapped to chromosome 1p36.3, which is a locus of multiple tumour-suppressor genes for many cancers, including h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…The p73 gene, encoding only DN-p73 transcripts in normal liver, may function as a tumour promoter rather than a tumour suppressor in this tissue, by interfering with wild-type p53 function Pozniak et al, 2000). This could explain why p73 is not mutated in HCC (Mihara et al, 1999). However, p53 gene is frequently mutated in HCC (Ozturk, 1999), as also demonstrated here in HCC-derived cell lines (Figure 2c).…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…The p73 gene, encoding only DN-p73 transcripts in normal liver, may function as a tumour promoter rather than a tumour suppressor in this tissue, by interfering with wild-type p53 function Pozniak et al, 2000). This could explain why p73 is not mutated in HCC (Mihara et al, 1999). However, p53 gene is frequently mutated in HCC (Ozturk, 1999), as also demonstrated here in HCC-derived cell lines (Figure 2c).…”
Section: Discussionmentioning
confidence: 51%
“…However, p53, but not the other family members, is considered a tumour-suppressor gene. For example, unlike p53, p73 de®ciency in mice does not lead to a cancerprone phenotype , and p73 gene is not mutated in human tumours, including hepatocellular carcinoma (HCC) Mihara et al, 1999). Presently, the reasons for this discrepancy are not known.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…For example, p73 and p63 are rarely mutated in tumors (Nomoto et al, 1998;Mihara et al, 1999;Yokomizo et al, 1999;Moll et al, 2001). However, both proteins have been found to play a role in development.…”
Section: Introductionmentioning
confidence: 99%
“…Jost et al (1997) showed that overexpression of p73 can activate the transcription of TP53-responsive genes like p21 wafl/cipl and inhibit cell growth in the same way as TP53 by inducing apoptosis. Mutation analyses for the p73 gene have been performed in lung carcinoma, oligodendrogliomas, prostatic carcinoma, neuroblastomas, colorectal carcinoma, oesophageal carcinoma and hepatocellular carcinoma (Kovalev et al, 1998;Mai et al, 1998aMai et al, , 1998bNimura et al, 1998;Nomoto et al, 1998;Sunahara et al, 1998;Ichimiya et al, 1999;Mihara et al, 1999). Except for two mutations in primary neuroblastomas resulting in amino acid substitutions in the C-terminal region of p73 , no other mutations have been reported.…”
mentioning
confidence: 99%